Aspectos anatomopatológicos da medula óssea na peritonite infecciosa felina - Luz, Flávia Serena da (2017)
Feline infectious peritonitis (FIP) is a highly contagious, progressive and invariably fatal viral disease of cats, and occasionally of wild felids, which results from antibody-mediated hypersensitivity reactions (types III and IV) in individuals incapable to produce a cell-mediated immune response. Although the prevalence of FIP is high worldwide, recent anatomopathological studies about this disease are scarce. Furthermore, the microscopic characteristics of the bone marrow of FIP-affected cats do not exist in the available literature. Based on this, the purpose of this dissertation is to describe possible bone marrow lesions seen in spontaneous cases of FIP. Therefore, the bone marrow collected systematically from the femoral diaphysis of 16 cats necropsied in the LPV-UFSM (Santa Maria, RS, Brazil), between January 2000 and June 2017, with a definitive diagnosis of FIP, were evaluated phenotypically (histopathology [hematoxylin and eosin] and histochemistry [Perls reaction]) and immunophenotypically (immunohistochemistry using anti-myeloid [MAC387] and anti-lymphoid [CD79αcy and CD3] markers). The results showed, regardless of the clinicopathological form of the disease (“dry” [noneffusive] or “wet” [effusive]), myeloid hyperplasia; erythroid hipoplasia; megakaryocytic dysplasia (dismegakaryocytopoiesis); and medullary plasmacytosis. In cases of “dry FIP”, but not in those of “wet PIF”, there was bone marrow and hepatic hemosiderosis. These lesions allowed establishing that cats with FIP develop myelodysplasia, a myeloproliferative lesion very similar to that reported in HIV-infected humans. It is suggested that, based on the findings described here, myelodysplasia is considered to be the main cause of hematological abnormalities observed in FIP, especially for non-regenerative anemia and thrombocytopenia, frequently developed by patients.